THE INFLUENCE OF INVESTMENT AND NET EXPORT ON THE ECONOMIC GROWTH IN INDONESIA (AUTOGRESSIVE DISTRIBUTED LAG MODEL) - Lismana Lismana; Michael Michael; Juliansyah Roy (Bajang Institute, 2022)
High net export growth does not guarantee high economic growth either. Likewise, the increase in foreign direct investment is not always followed by an increase in Indonesia's economic growth rate. The purpose of this study is to determine and analyze the influence of investments and net exports on Indonesia's economic growth and to determine the effect of different investment periods on Indonesia's economic growth in the years 2005-2020. The results showed that economic growth fluctuated, so the autoregressive distributed lag results started with a Trace Statistics value that was small than the allowable level, so all variables were no cointegrated. From this it can be concluded that there is no long-term relationship between the variables of economic growth, investment and net exports. The results of the Optimal lag test concluded that the appropriate model for the method in this study is autoregressive distributed lag because it has a smaller error.